A study of decision making process in crude palm oil trading: TH Plantations Berhad / Mohd Hafiz Zakaria - Zakaria, Mohd Hafiz (Faculty of Business and Management, 2010)
The purpose of this study is to determine the decisions making process that should be followed by the members of marketing department in TH Plantations Berhad in order to improve the sales transaction process between buyer and sellers. In addition, this study also will help to gain a better knowledge and understanding decisions making on choosing a buyer. The decision process will help the marketers to identify the step and actions should they need to perform before making purchase decision. In order to complete this study, several methods of research methodology is used to finalize and make conclusion on the findings of the result. The research methodology consists of data collection method, data presentation and work schedule were deeply discussed in the latter chapters. As for this study, it expected that the THP decision making on selecting a buyer could be derive based on the decisions making process analysis. The study will compare the current marketing strategy being implied by marketing staff of THP based on decision making process with the actual technique suggested by scholars. Besides that, the result of this study will prove that there are flaws on strategy implied by marketers of THP.